CHARACTERISATION OF ADHESIN AND RECEPTOR MOLECULES IN THE GASTRIC EPITHELIUM OF MICE: PATHOGENESIS STUDY AND DEVELOPMENT OF DIAGNOSTIC MATERIALS FOR HELICOBACTER PYLORI INFECTION - Hamong Suharsono (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
This research focuses on the characterization of adhesin and receptor molecules on the gastric epithelium of mice to understand the pathogenesis mechanisms of Helicobacter pylori infection and its potential in the development of diagnostic materials. Infection by H. pylori begins with the colonization process on the surface of the gastric mucosa, where the bacteria use various attachment factors, including pili and outer membrane proteins (OMPs), to adhere to host cells. This study involves the isolation of H. pylori pili using the pili cutter method and the isolation of hemagglutinin protein from OMPs through centrifugation and dialysis processes. These proteins were then analyzed through hemagglutination assays, SDS-PAGE, Western blotting, as well as adhesion and immunohistochemistry tests to evaluate the specific interactions between H. pylori adhesins and gastric epithelial cells. The results identified adhesins such as BabA and SabA, which play a crucial role in H. pylori adhesion to the gastric epithelium, particularly by binding to Lewis blood group antigens. Additionally, it is suspected that there are other adhesin proteins that may originate from the tip of H. pylori pili associated with the type IV secretion system (T4SS). Hemagglutination assays demonstrated significant hemagglutination activity in the adhesin proteins, while Western blotting results showed specific interactions between the adhesin proteins and antibodies. Furthermore, adhesion and immunohistochemistry tests confirmed the ability of H. pylori adhesins to adhere to mouse gastric epithelial cells. These findings enhance our understanding of the role of adhesins in the pathogenesis of H. pylori infection, particularly during the early stages of colonization, and open up opportunities for the development of diagnostic materials that can detect the presence of H. pylori based on adhesin-receptor interactions. This research provides a scientific foundation for the development of new strategies in the diagnosis and management of H. pylori infection.